Motivation of Students of The Faculty of Teacher Training and Education In Participating In Religious Learning and Worship Muamalah Model Baitul Arqam University of Muhammadiyah Surakarta - Saifudin; Ahmad Nurrohim; Muthoifin; Yeti Dahliana; Fuadi; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2024)
The objectives to be achieved in this study are to find out: Motivation of Students of the Faculty of Teacher Training and Education in participating in Islamic Studies Learning 1 and 2 Baitul Arqam Model of the University of Muhammadiyah Surakarta. The type of research that the author conducts is in the form of field research using a qualitative approach, namely research whose procedures produce descriptive data in the form of written or spoken words from people and actors observed. The methods used to collect data are: First, the guided interview method (Guide interview) is an interview conducted by the interviewer with a series of complete and detailed questions. Second, the questionnaire method is a data collection technique carried out by giving a set of questions or written statements to respondents to answer". These two methods the author used to obtain data in the second year on the Motivation of Students of the Faculty of Teacher Training and Education in participating in Religious and Worship Learning and Muamalah Model Baitul Arqam University of Muhammadiyah Surakarta. Third, to analyze the collected data, researchers use data analysis, namely by qualitative descriptive analysis, that is, the data that appears in the form of written or spoken words of people or observed behavior, namely through interviews, observations and documentation processed through recording and others then compiled in expanded text.